2019
DOI: 10.1007/s10826-019-01481-x
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Grief Therapy: Pilot Open Trial of a Novel Intervention for Bereaved Children and Adolescents

Abstract: Objectives This study describes a pilot open trial of Multidimensional Grief Therapy, an assessment-driven, phasic individual therapy for bereaved youth. This study provides a preliminary outcome evaluation with respect to maladaptive grief reactions, post-traumatic stress symptoms, and depressive symptoms in bereaved youth. Methods The sample consisted of 65 bereaved youth (ages 6-17 years, M = 11.62, SD = 2.76; 53% female; 33.3% Hispanic, 31.8% African American/Black, 27.3% Caucasian, 6.1% mixed/biracial, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…In the DSM‐5 , PCBD is a provisional diagnosis included in the appendix as an invitation for further research. Items on the PCBD Checklist are rated using a 5‐point scale ranging from 0 ( not at all ) to 4 ( all the time ) and have shown good convergent and discriminant validity with symptoms of posttraumatic stress and depression (Kaplow et al., 2018) as well as good sensitivity to therapeutic change (Hill et al., 2019). In the current study, summative subscale scores corresponding to the primary grief symptom clusters described in PCBD Criterion B and C were used.…”
Section: Methodsmentioning
confidence: 99%
“…In the DSM‐5 , PCBD is a provisional diagnosis included in the appendix as an invitation for further research. Items on the PCBD Checklist are rated using a 5‐point scale ranging from 0 ( not at all ) to 4 ( all the time ) and have shown good convergent and discriminant validity with symptoms of posttraumatic stress and depression (Kaplow et al., 2018) as well as good sensitivity to therapeutic change (Hill et al., 2019). In the current study, summative subscale scores corresponding to the primary grief symptom clusters described in PCBD Criterion B and C were used.…”
Section: Methodsmentioning
confidence: 99%
“…There were not enough studies with between-group comparisons or follow-up to include in calculation of effect sizes in the meta-analysis, we synthesize these here. Only 3 of the 27 studies included an active treatment comparison (i.e., between-groups comparison) in an RCT design [26,29,30]. Similarly, few studies (n = 8; 30%) included a follow-up, ranging from 6 weeks [31] to 12 months [26,32].…”
Section: Narrative Synthesismentioning
confidence: 99%
“…Considering that some studies did not measure grief, and a wide variety of grief measures were used across studies, we were unable to test-baseline grief symptoms as a moderator in the meta-regression. However, among CBT interventions, groups where the participants had clinically significant grief or PTSD symptoms typically reported larger reductions in grief, anxiety, and depression [26,29,30,32,[35][36][37][38][39], compared to non-clinical samples (e.g., inclusion was "has experienced a loss"; [40][41][42][43][44]. Sandler et al [46] was the one outlier, with no clinical inclusion criteria but showing a large decrease in depression at posttest.…”
Section: Narrative Synthesismentioning
confidence: 99%
“…Third, uncontrolled studies (14,15) have indicated that cognitive-behavioral therapy for childhood traumatic grief, targeting both traumatic stress and grief following unnatural deaths, successfully alleviates disabling grief. More recently, an uncontrolled pilot study showed that multidimensional grief therapy yielded promising effects (16).…”
Section: Articlesmentioning
confidence: 99%